The impact of food animal welfare on human wellbeing: scientific and Islamic perspective - Zaw, Cho Cho; Min @ Mohd Omar, Myat (2019)
Abstract: Animal warfare includes consideration for all aspects of animal welfare and meeting their physical and mental needs. It generally concerns at keeping, handling, providing nutrition, disease prevention of animals especially in three important stages which are production, transportation, and slaughtering process for food animals. From the holistic medicine point of view, human wellbeing covers all aspects of physical, social, psychological and spiritual. About 80 percent of the human population of the world relies animals for their food in which the food animals serve as the main source for most of protein, fats, iron, and some vitamins. World Health Organization (WHO) reported that chronic diseases such as obesity, diabetes, cardiovascular and dental diseases, cancer and osteoporosis are related with human diet and nutrition. This paper aims to explore the impact of food animal welfare to human wellbeing by using literature search as a methodology. The Islamic perspectives as well as the scientific findings in the related area are presented in this paper. Islam provides fundamental ethical guidelines in dealing with animals and highlights the importance of halalan toyyiban to achieve meat quality for human wellbeing. The scientific findings supported that mishandling of animals while keeping or slaughtering lead them to face physical and psychological stress which in turn affect the quality of the meat and chances of getting foodborne diseases. Both scientific and Islamic perspectives pointed out the requirement of animal welfare for human well-being. Thus, the welfare of food producing animals such as ruminants and poultry should not be neglected since they have positive and negative consequences on human wellbeing. It should be implemented and integrated the existing and established guidelines of the meat industry and the Islamic perspectives so that to achieve the optimal value of human wellbeing.